Dividend Policy of Banking Firms in Nepal: A Survey of Managerial Perspectives - Rana, Surya B. (Journal of Business and Social Sciences Research, 2022)
This paper analyses the views of managers of banking firms in Nepal to understand their perceptions towards dividend theories and factors affecting dividend policy. Based on a mail survey among 79 directors and CEOs of banking firms in Nepal during the months January to March 2022, the study suggests that managers prefer at most the combination of cash and stock dividend to be distributed to their shareholders. With respect to their preferences towards given form of dividend payments, managers claim that they generally go with shareholders’ preferences in deciding the forms of dividend payments. The study results further demonstrate strong support for signalling and bird-in-hand explanations of dividend theories. Among the 14 factors affecting dividend policy, the study reveals that firm’s level of current earnings, including the pattern of past earnings and stability of earnings are important factors in determining dividend policy of banking firms in Nepal. The survey evidence documented in this study further verifies the significance of signalling hypothesis in recent period in case of Nepal to explain why managers prefer to pay dividend. The main implication of the findings of this study is that it explores, in the changing context of meeting regulatory capital requirements, how the banking managers perceive about dividend policy of Nepalese banking firms. The finding of the study is primarily useful to investors seeking for investment in dividend paying banking firms in Nepal